A group of ‘giants’ houses’ recently discovered in Salmas Region, Iran - Khanmohammadi, Behrouz; Dan, Roberto; Garavand, Afrasiab (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
This paper describes a group of recently discovered structures identified during survey activities carried out in 2019 by the authors. All the newly discovered sites are located in the Shepiran Rural District of the Kohsar District, which is part of Salmas County in West Azerbaijan Province, Iran. The group of buildings exhibits interesting and unusual features. To date we have had the opportunity to study eighteen specimens of this type of building. These buildings are very similar in size and shape to the so-called ‘Giants’ Houses’ well attested in south-eastern Turkey, especially in the southern part of Lake Van, and in Armenia. Although the architectural simplicity of these structures, some suggestions regarding their functional interpretation have been proposed.